Peningkatan Minat Pembelajaran Taman Pendidikan Al Qur’an (TPA) di Masjid Anni’mah Kemlayan: Increasing Interest in Al Qur’an Education at Anni’mah Mosque TPA in Kemlayan - Lafith Baror Isthibar; Faezal Dwi Anugrah; Muhammad Zaky Albani; Anas Vio Sadewa; Gea Dwiki Yustanto; Muhammad Abbdee Negara; Ahmad Nurrohim (Litera Academica Publishing, 2025)
The Community Service and Learning Field Practice (PKLPP) program at Anni’mah Mosque, Kemlayan, was implemented as a student initiative to strengthen religious character education within the community. The main activities included mentoring at the Qur’anic Learning Center (TPA) and participating in the Sunday morning religious study sessions. Mentoring was conducted collaboratively with local teachers by providing guidance in reading the Qur’an, Iqra’, memorizing short surahs, and daily prayers. Students also engaged in Sunday study sessions to observe communicative preaching methods used in the community. The results showed an increase in students’ learning interest, although challenges such as a shortage of permanent teachers and declining youth participation due to digital distractions remain. This program is expected to foster synergy between students, mosque management, TPA teachers, parents, and the community in shaping a Qur’anic generation with noble character.